MINIMALLY INVASIVE METHODS OF SURGICAL TREATMENT OF ENDOCRINE OPHTHALMOPATHY - O. V. Levchenko; A. A. Kalandari; A. Yu. Grigoriev; N. Yu. Kutrovskaya; О. N. Timofeeva (Oftalʹmologiâ)
“Balanced” bone  decompression of the  orbit was  performed in a patient  with endocrine ophthalmopathy, CAS3, OD=30 mm,  OS=31 mm with the use of minimally invasive transconjunctival approaches and frameless neuronavigation. At the first stage the preoperative computed  tomography  of  the  orbits   was  imported   into  the  navigation  software,  and  then   marked  the  area of  the  proposed resection of the  orbit  walls. Further, in the  operating room,  the  patient  was  registered in the  navigation system. To perform  bone decompression of the orbit and lipectomy, we used  preseptal, transcaruncular and lateral retrocanthal approaches. These approaches are  transconjunctival and  do not  leave postoperative scars. Upon completion  of the  orbitotomy, its accuracy and  dimensions were determined by the intraoperative pointer of the neuronavigation system.Results. The postoperative period was uneventful. In the early postoperative period there was a regression of exophthalmus OD=26 mm,  OS=27  mm,  closure  of the  eye gap,  but retraction of the eyelids remained. When examined 3 months after the operation, the exophthalmic regression was OD=23 mm, OS=24 mm, retraction of the  eyelids — 1 mm,  with lead — finishing to the  lateral  adhesion. When  examined  after  6 months — the  position of the  eyeballs in orbit: ОD=21 mm,  ОS=22  mm,  retraction of the  eyelids is not present, there is no violation of oculomotorics, complications were not recorded. A satisfactory result  was  obtained.Conclusion. Minimally invasive transorbital approaches allow the  transconjunctival acces to all orbital walls to perform  decompression of the  orbit and lipectomy without cutaneous incisions,  to achieve good cosmetic and functional results. And the intraoperative use  of the neuronavigation system ensures  the bone decompression of the orbit in full. The technique is promising  and requires further  randomized  studies.